The Profiles of Body Image Associate With Changes in Depression Among Participants in Dance Movement Therapy Group - Pylvänäinen, Päivi; Hyvönen, Katriina; Muotka, Joona (Frontiers in Psychology, 2020)
This mixed-methods study analysed the body image quality of 143 patients with depression. The participants received a 20x75 min dance movement therapy (DMT) group treatment, sessions twice a week. Body Image Assessment (BIA) was the data collection tool, with pre-, post and and 3-mos follow-up assessments. Pre-intervention body image quality characteristics were low energy and activity levels, discomfort, shame and disgust towards the body, tension in social interactions. On the BIA scores, a statistical method of Latent Profile Analysis was utilized to identify participant profiles in the data. The two identified profiles were participant with initial negative body image and participant with initial neutral body image. Depression symptoms were measured with BDI, and symptoms decreased for both participant profiles following the DMT intervention. The neutral profile participants had a significantly lower depression level, better energy level, and more frequently used mindfulness factors of acting aware, non-judgementality and non-reactivity (measured with FFMQ). Findings suggest a systemic interaction between depression symptoms, body image, attachment style, activity level, and mindfulness skills. In an interactive DMT setting it is possible to address all of these factors simultaneously.